The Legend of Meriam Puntung: Oral Tradition Narratives and the Construction of Collective Memory in the Malay Community - Maysaroh Maysaroh; Putri Wandini; Irmayana Irmayana; Tegar Tri Wibowo; Farhan Aziz Batubara; Yusra Dewi Siregar (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
The legend of Meriam Puntung is a significant part of the oral tradition among the Malay community, serving as both a historical narrative and a medium for collective memory construction. This study explores how the legend has been transmitted across generations, its role in shaping historical consciousness, and the extent to which it reflects the identity of the Malay people. Using Jan Vansina’s oral tradition theory and Paul Connerton’s theory of collective memory, this research examines the dynamics of storytelling, the transformation of the narrative over time, and its function in preserving historical knowledge. Employing a qualitative approach, data were collected through in-depth interviews with cultural figures, textual analysis of historical sources, and field observations at the Meriam Puntung site. The findings reveal that the legend has undergone adaptations, influenced by sociopolitical changes, while maintaining its core symbolism of resistance and local identity. Furthermore, the study highlights how the site itself serves as a tangible anchor for collective remembrance, reinforcing historical continuity. This research contributes to the discourse on the interrelation between oral tradition and historical consciousness, emphasizing the role of storytelling in shaping collective memory and identity formation within the Malay cultural framework.